2018
DOI: 10.1002/ncp.10060
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Calorie and Protein Intake of Very Low Birth Weight Infants Receiving Mother's Own Milk or Donor Milk When the Nutrient Composition of Human Milk Is Measured With a Breast Milk Analyzer

Abstract: DBM provides comparable nutrient intake to MOM at a higher enteral feeding volume. However, both types of human milk failed to meet energy needs with standard fortification regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Given reports of inferior growth with DM [4,7,10,11,12,13] and concerns regarding low protein content [23], our feeding protocol supplemented all DM with protein in addition to standard fortification, regardless of infant growth. Although we did not analyze milk samples, this protein supplementation presumably increased the nutritional content of DM and may explain the lack of effect of DM on short-term growth [30], providing additional evidence to support this widely-used practice for DM. Similar to the DoMINO trial [9], the majority of infant feedings in both groups consisted of MOM, even when excluding infants fed exclusive MOM, thus limiting our ability to study the effects of high-dose DM.…”
Section: Discussionmentioning
confidence: 99%
“…Given reports of inferior growth with DM [4,7,10,11,12,13] and concerns regarding low protein content [23], our feeding protocol supplemented all DM with protein in addition to standard fortification, regardless of infant growth. Although we did not analyze milk samples, this protein supplementation presumably increased the nutritional content of DM and may explain the lack of effect of DM on short-term growth [30], providing additional evidence to support this widely-used practice for DM. Similar to the DoMINO trial [9], the majority of infant feedings in both groups consisted of MOM, even when excluding infants fed exclusive MOM, thus limiting our ability to study the effects of high-dose DM.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the mean protein content decreases during lactation, while the nutrient needs of VLBW infants remain high ( 28 , 29 ). In addition, although it has been reported that donor human milk provides nutrients comparable to mother's milk, preterm infants fed donor human milk fortified similarly to fresh mother's milk according to standard methods showed an increased risk of postnatal growth restriction ( 30 , 31 ). In contrast, it has been reported that fortification of donor human milk to reach 3.5 g/kg of protein intake is associated with significantly greater weight gain and head growth in VLBW infants than feeding a formula-based diet ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although it has been reported that donor human milk provides nutrients comparable to mother's milk, preterm infants fed donor human milk fortified similarly to fresh mother's milk according to standard methods showed an increased risk of postnatal growth restriction ( 30 , 31 ). In contrast, it has been reported that fortification of donor human milk to reach 3.5 g/kg of protein intake is associated with significantly greater weight gain and head growth in VLBW infants than feeding a formula-based diet ( 30 ). In addition, targeted fortification of human milk seems to represent an optimal strategy to prevent postnatal growth restriction ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our observations, we have submitted recommendations to the neonatal clinical guideline development group to consider the lower dose of CC at 5 mg/kg (elemental caffeine of 2.5 mg/kg) as the standard starting maintenance dose and to appropriately incorporate additional nutritional input or consideration if ELBW and VLBW infants are maintained on a relatively higher dose of caffeine for prolonged periods. 39 A reaudit is recommended for the audit cycle completion in 2019.…”
Section: Discussionmentioning
confidence: 99%